Characterization of HCV Resistance from a 3-Day Monotherapy Study of Voxilaprevir, a Novel Pangenotypic NS3/4A Protease Inhibitor. Issue 4 (May 2018) - Lawitz, Eric; Yang, Jenny C; Stamm, Luisa M; Taylor, James G; Cheng, Guofeng; Brainard, Diana M; Miller, Michael D; Mo, Hongmei; Dvory-Sobol, Hadas
Background: Voxilaprevir (VOX; GS-9857) is a pangenotypic HCV NS3/4A protease inhibitor (PI) with potent antiviral activity against HCV genotypes (GTs) 1–6 and improved coverage of GT1 NS3 resistance-associated substitutions (RAS) associated with other HCV PIs. In a 3-day Phase Ib monotherapy study in patients infected with HCV GT1a, 1b, 2, 3 and 4, VOX was well-tolerated and resulted in maximal mean viral load reduction >3 log10 IU/ml at the 100 mg dose across all genotypes evaluated. This report characterizes the HCV NS3 RAS in the study. Methods: The NS3 gene was amplified and successfully deep sequenced using MiSeq for 66 patients at baseline and 61 patients post-baseline using 15% and 1% assay cutoffs. Results: With a 15% assay cutoff, pretreatment HCV NS3 RAS were present in the HCV of 38% (9/24) of patients with GT1a and 5% (1/19) with GT3a; there were no pre-treatment NS3 RAS present in patients with GT1b ( n =6), GT2 ( n =7) or GT4 ( n =4). In patients with and without pretreatment NS3 RAS, ≥3.4 log10 mean maximal viral load reductions over 3 days of VOX administration were observed. The majority of patients did not have detectable treatment-emergent NS3 RAS and only 12% (7/53) and 26% (14/53) had emergent NS3 RAS using 15% and 1% cutoffs, respectively. No NS3 RAS were detected in patients with GT2 or GT4. A156T or A156V were the most prevalent emergent NS3 RAS in patients with GT1a or GT1b infection, but were not observed in patients with GT3 infection. Conclusions: The lack of selection of NS3 RAS in the majority of patients demonstrates a high resistance barrier for VOX. ClinicalTrails.gov identifier NCT02185794.